The Payload Design of the CUbesat Solar Polarimeter (CUSP), for Space Weather and Solar Flares X-Ray Polarimetry - Giovanni Lombardi; Sergio Fabiani; Ettore Del Monte; Emanuele Di Meo; Andrea Lopez; Marco Camponeschi; Marco E. Biancolini; Daniele Brienza; Immacolata Donnarumma; Silvia Natalucci; Andrea Terracciano; Emanuele Zaccagnino (Engineering Proceedings)
The CUbesat Solar Polarimeter (CUSP) project is a CubeSat mission orbiting the Earth aimed to measure the linear polarization of solar flares in the hard X-ray band by means of a Compton scattering polarimeter. CUSP is a project in the framework of the Alcor Program of the Italian Space Agency aimed to develop new CubeSat missions. It is approved for a Phase B study. In this work we describe some design solutions adopted for the most important design drivers of the payload. In particular, we report on the payload preliminary multi-physical design, including an orbital thermal environment preliminary assessment and a implementation of the static/dynamic finite element analysis. Moreover, a method for topology optimization of relevant components is discussed.